2002
DOI: 10.1592/phco.22.5.303.33189
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Acetaminophen or Nonsteroidal Antiinflammatory Drugs and Risk of Developing Ovarian, Breast, or Colon Cancer

Abstract: We found no evidence for a decreased ovarian cancer risk for women with regular acetaminophen or NSAID exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 31 publications
5
84
0
1
Order By: Relevance
“…Meier et al (2002)found that those with 30 paracetamol prescriptions or more had an OR of 0.8 (95% CI: 0.7, 1.0) compared to nonusers. Harris et al (1999) reported an OR of 0.84 among paracetamol users in a cohort of 32 505 women.…”
Section: Discussionmentioning
confidence: 99%
“…Meier et al (2002)found that those with 30 paracetamol prescriptions or more had an OR of 0.8 (95% CI: 0.7, 1.0) compared to nonusers. Harris et al (1999) reported an OR of 0.84 among paracetamol users in a cohort of 32 505 women.…”
Section: Discussionmentioning
confidence: 99%
“…No information was available on over-the-counter (OTC) NSAID use (including that from non-pharmacy outlets) but there is little evidence of large-scale OTC purchasing of NSAIDs in the UK, especially in the middle aged and elderly. (Meier et al, 2002) Pancreatic cancer diagnoses were not validated and some misclassification of diagnoses may have occurred within the GPRD system but we excluded very elderly subjects, in which diagnostic accuracy may be a particular problem; also, all cancer codes were reviewed and cases with inconsistent coding were excluded. Furthermore, cancer diagnoses in GPRD appear to be a reliable record of incident cancer diagnoses and have been shown to concord with original medical records in 95% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a recent study reported an increased risk of pancreatic and prostate cancer among NSAID users (Langman et al, 2000). Data regarding the risk of lung, breast, and ovarian cancer among NSAID users are conflicting (Peto et al, 1988;Paganini-Hill et al, 1989;Schreinemachers and Everson, 1994;Egan et al, 1996;Harris et al, 1996Harris et al, , 1999Cramer et al, 1998;Akhmedkhanov et al, 2001;Moysich et al, 2001;Meier et al, 2002).…”
mentioning
confidence: 99%